In situ generation of less accessible Boc-imines from aldehydes: construction of a quaternary carbon by the Mannich reaction or unprecedented aldol reaction. Issue 21 (17th May 2017) - Kano, Taichi; Homma, Chihiro; Maruoka, Keiji
Abstract : Mannich reactions of β-dicarbonyls with in situ generated less accessible Boc-imines from aldehydes were achieved. Abstract : In situ generation of less accessible N -Boc-protected imines from aldehydes and their application to the direct three-component Mannich reaction with β-dicarbonyls were realized. The catalyst-free aldol reaction of ynals with β-dicarbonyls was also developed.